Genetic diversity of Moniliophthora roreri using Amplified Fragment Length Polymorphism (AFLPs) (2018)
Cacao cultivation is affected by the Moniliophthora roreri phytopathogen, which causes large production losses in Norte de Santander. This study shows the results obtained using the AFLPs of M. roreri. The kit for analysis system II was standardized and applied to 56 samples of M. roreri, isolated from nine municipalities. The combination with the highest number of polymorphisms was E-ACC/M-CAA. With 90 bands and a smaller number of alleles (6), the E-ACG/M-CAA combination yielded 90 bands and a larger number of alleles (23); the E-AAC/M-CAA combination had 94 bands and alleles (12). The data analysis was carried out according to the dendrogram of similarity or genetic distances of Nei, obtaining five groups with a high variability between samples, from 6.5 to 58%. By combining the morphological and molecular information, the level of genetic diversity in Moniliophthora roreri was determined.